Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Backside: Luisa Medina, Chris Marie Brown and Garrick Brown; facing l to r: ?, John Joyce, Janie Munoz, Alice Mendoza and ? Mendoza